THE PROBLEM OF DEVELOPMENT OF PERCEPTION AND IMAGINATION OF WORKS OF ART IN SCHOOLCHILDREN BY THE SCIENCE OF FINE ARTS AND ITS STUDY BY FOREIGN SCHOOLS (Euro-Asia Conferences, 2021)
This article provides information on the scientific views of foreign scholars on the development of aesthetic and spiritual education in students through the science of fine arts and the science of fine arts